Convergent synthetic methodology for the construction of self-adjuvanting lipopeptide vaccines using a novel carbohydrate scaffold - Fagan, Vincent; Toth, Istvan; Simerska, Pavla (Beilstein Journal of Organic Chemistry, 2014)
A novel convergent synthetic strategy for the construction of multicomponent self-adjuvanting lipopeptide vaccines was developed. A tetraalkyne-functionalized glucose derivative and lipidated Fmoc-lysine were prepared by novel efficient and convenient syntheses. The carbohydrate building block was coupled to the self-adjuvanting lipidic moiety (three lipidated Fmoc-lysines) on solid support. Four copies of a group A streptococcal B cell epitope (J8) were then conjugated to the glyco-lipopeptide using a copper-catalyzed cycloaddition reaction. The approach was elaborated by the preparation of a second vaccine candidate which incorporated an additional promiscuous T-helper epitope.
Keywords: amino acid lipidation; cycloadditon reaction; multivalent glycosystems; peptide vaccine; tetrapropargyl glucopyranose